2012
DOI: 10.1111/j.1742-1241.2012.02903.x
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin add-on to low dosage sulphonylureas: efficacy and safety of combination therapy on glycaemic control and insulin secretion capacity in type 2 diabetes

Abstract: The combination therapy with sitagliptin and low dosage sulphonylureas was safe and effective for glycaemic control. Glucagon loading test indicated that 1 year administration of sitagliptin and sulphonylureas preserved insulin secretion capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 24 publications
3
41
1
1
Order By: Relevance
“…Insulin secretion capacity did not predict the efficacy of combination therapy in this study. This result is consistent with a previous study [7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Insulin secretion capacity did not predict the efficacy of combination therapy in this study. This result is consistent with a previous study [7].…”
Section: Discussionsupporting
confidence: 83%
“…This recommendation should be evaluated in terms of its impact on the frequency of severe hypoglycemic episodes and any dosedependency associated with low-dose glimepiride. Recently, Harashima et al reported that combination therapy with sitagliptin and low-dose (≤2 mg/day) glimepiride was safe and effective for glycemic control in Japanese patients with type 2 diabetes [7]. The present study is the first to investigate the dose-dependency of glimepiride, below 2 mg (0.5 mg, 1 mg, and 2 mg), in combination with sitagliptin.…”
Section: Discussionmentioning
confidence: 81%
“…Небольшие по объему пилотные иссле-дования показали возможность снижения альбуминурии у больных СД2 на фоне терапии ситаглиптином [82][83][84]. Прослежена взаимосвязь выраженности антиальбуми-нурического эффекта препарата с исходной величиной альбуминурии: наиболее заметное снижение ЭАМ про-слеживалось у больных с макроальбуминурией [82,85].…”
Section: ингибиторы дпп-4unclassified
“…Patients with greater degree of albuminuria at baseline had more decline in mean UACR with sitagliptin [29]. In a 52-week single-arm study, sitagliptin added to sulphonylureas reduced HbA1c by 9 mmol/mol (0.8%), decreased UACR from 76.2 ± 95.6 to 33.0 ± 48.1 mg/g, and elicited a decrease in blood pressure [30]. An ongoing phase 4 RCT is designed to explore effect of sitagliptin given in addition to ACE inhibitor or ARB in reducing microalbuminuria in patients with T2DM (NCT02048904).…”
Section: Pharmacotherapy For Dkdmentioning
confidence: 99%